2009
DOI: 10.4049/jimmunol.0803648
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L Blockade Prevents Anergy Induction and Enhances the Anti-Tumor Activities of Glycolipid-Activated Invariant NKT Cells

Abstract: Invariant NKT (iNKT) cells recognize glycolipid Ags, such as the marine sponge-derived glycosphingolipid ␣-galactosylceramide (␣GalCer) presented by the CD1d protein. In vivo activation of iNKT cells with ␣GalCer results in robust cytokine production, followed by the acquisition of an anergic phenotype. Here we have investigated mechanisms responsible for the establishment of ␣GalCer-induced iNKT cell anergy. We found that ␣GalCer-activated iNKT cells rapidly up-regulated expression of the inhibitory costimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
197
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(212 citation statements)
references
References 60 publications
13
197
1
1
Order By: Relevance
“…These phenomena were not observed in our phenyl-glycolipids, which had been reported to have greater TCR signaling than a-GalCer because of stronger binding avidity and greater binding stability of CD1d-phenyl glycolipid complexes for iNKT TCR (8). Our findings were in line with the report that a-GalCer induced the expression of PD1 and cbl-b, which might contribute to NKT cell anergy (9,12). It was also consistent with the reports that egr2/3 could regulate the expression of PD1 and cbl-b (41) to cause T cell tolerance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These phenomena were not observed in our phenyl-glycolipids, which had been reported to have greater TCR signaling than a-GalCer because of stronger binding avidity and greater binding stability of CD1d-phenyl glycolipid complexes for iNKT TCR (8). Our findings were in line with the report that a-GalCer induced the expression of PD1 and cbl-b, which might contribute to NKT cell anergy (9,12). It was also consistent with the reports that egr2/3 could regulate the expression of PD1 and cbl-b (41) to cause T cell tolerance.…”
Section: Discussionsupporting
confidence: 82%
“…Parekh et al (9) reported that administration of a-GalCer induced expression of programmed death 1 (PD1) on NKT cells, which contributed to NKT cells anergy. PD1 is a member of the costimulatory molecules CD28 family and is expressed on activated T, B, NKT cells, monocytes, and dendritic cells but not on naive T cells (10).…”
mentioning
confidence: 99%
“…In conventional T cells, PD-1 is not expressed on naive T cells, but it is inducibly expressed after T cell activation (36). In recent reports, PD-1 and its ligands have been implicated in the induction and maintenance of T cell and NKT cell anergy (37,38,42,43). In our previous report, we demonstrated that NKT cell dysfunction was associated with upregulation of inhibitory receptor PD-1 in active tuberculosis, and it was partially recovered by blockade of PD-1 (44).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent reports have shown that PD-1-PD-L interaction is involved in the induction and maintenance of NKT cell anergy (37,38). To determine whether MAIT and NKT cell dysfunctions are related to PD-1, we examined the expression levels of PD-1 in the peripheral blood samples of 11 SLE patients, 10 RA patients, and 10 HCs (Fig.…”
Section: Elevated Pd-1 Expression In Mait Cells Nkt Cells and T Celmentioning
confidence: 99%
“…Strikingly, whereas free a-GalCer induced iNKT cell hyporesponsiveness, iNKT cells from mice previously inoculated with a-GalCer-loaded DCs maintained their capacity to reactivate. Of note, free a-GalCer induced enhanced PD-1 expression on iNKT cells, an inhibitory molecule that causes iNKT cell hyporesponsiveness (32,33), whereas a-GalCer-loaded DCs failed to do so (Fig. 1C).…”
Section: Cd8amentioning
confidence: 99%